Exploring the Relationship Between Volunteerism, Inclusivity, and Democracy in Norwegian Sports - Svein Erik Nordhagen (Canadian Journal of Nonprofit and Social Economy Research)
The Norwegian sport model is widely recognized for its emphasis on inclusivity, democratic governance, and strong tradition of volunteerism. This article examines the sustainability of relying on volunteers in Norwegian sports and whether the high level of volunteerism affects democracy in sport organizations. Drawing on academic literature and national statistics, this article highlights the significant contributions of voluntary work to Norwegian organized sports. However, shifts toward more individualized and short-term volunteering may threaten the sustainability of this model. Moreover, while the structures within Norwegian sport organizations may offer opportunities for democratic learning, there are also some limitations. The article concludes that, while the Norwegian sport model remains a successful example of community-based sports,  sport organizations must adapt to a changing societal landscape.